Turkey : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper analyzes the capital flows in Turkey. The empirical analysis in this paper uses exchange market pressure index to identify the determinants of capital flows to Turkey. It is observed that exchange market pressures in Turkey seem to a degree, larger than in other emerging economies, and to be linked to risk factors, both global and country specific. In particular, there seems to be a stronger link to the interest rates in advanced economies, which given forthcoming tightening of the U.S. monetary policy, is likely to intensify pressures on lira.